3D numerical modelling and experimental validation of an asphalt solar collector. (5th November 2017) - Alonso-Estébanez, Alejandro; Pascual-Muñoz, Pablo; Sampedro-García, José Luis; Castro-Fresno, Daniel
Highlights: An asphalt solar collector has been characterized by means of 3D numerical modelling. A finite volume approach has been considered for the CFD simulation. Lab-scale experimental tests were performed for validation purposes. Several grid sizes and viscous models were considered for the validation of the model. Energy collection and performance were determined per unit of area, flow rate, irradiance or thickness. Abstract: Research about renewable technologies for thermal energy collection is crucial when critical problems such as climate change, global warming or environmental pollution are concerned. Transforming solar energy into thermal energy by means of asphalt solar collectors might help to reduce greenhouse gas emissions and fossil fuel consumption. In this paper, a laboratory-scale asphalt solar collector formed by different slabs has been characterized by applying numerical techniques. An experimental test where the thermal performance of the collector was determined for three values of heat exchange fluid flow rate was carried out for the validation of the numerical model. Then, the CFD model was used to analyse the thermal response of the collector according to the following parameters: flow rate, solar irradiance, size and thickness. Results show that increasing values of heat exchange fluid flow rate result in better thermal performances. Likewise, increasing values of irradiance and size of the collector lead to higher values of thermal performance, although other parameters should also be considered for the final design of the system. Finally, under the conditions here considered, the thickness of the collector turned out not to be as significant as expected in relation to its thermal response. The combination of experimental tests and CFD codes can be considered a powerful tool for the characterization of asphalt solar collectors without incurring significant costs related to experimental field tests.